Self-reinforced hybrid polyethylene/MCM-41 nanocomposites: in-situ polymerisation and effect of MCM-41 content on rigidity - Campos, João M. (2013)
The synthesis of self-reinforced polyethylene-based materials prepared by in-situ polymerisation is described. The methodology developed uses MCM-41 mesoporous material in a triple role: as catalyst carrier for ethylene polymerisation within its pores and channels in a first stage, as nanofiller of the formed polyethylene matrixdur ing its useful lifetime and, finally, as promoter for long-term waste disposal. As evidenced by FTIR analysis, when the polymer is formed under these confined conditions different interactions between the MCM-41 material and the polyethylene matrix occur, when compared to simple blends. The influence of the filler content on the rigidity of the resulting nanocomposites is analysed by microhardness measurements and corroborated by the storage modulus values: a significant increase in rigidity is observed as the filler contents rises. In addition, thermogravimetric studies show interesting features concerning the degradability of these materials. The catalytic action of MCM-41 during degradation involves a reduction of the energetic requirements for their cracking and, therefore, a positive environmental impact.